The effects of the four strands by Paul Nation on students’ vocabulary acquisition at a lower and upper secondary school in Kien Giang province - Nguyễn Kiên Giang (Trường Đại học Trà Vinh, 2023)
With the growing attention to the problem mentioned above, the current study aimed to scrutinize the effects of the four strands on learners' English vocabulary acquisition. Remarkably, the study examined whether the four strands could improve learners' English vocabulary acquisition. Moreover, their attitudes toward the application of the four strands were taken into consideration.